2019
DOI: 10.1177/2333794x19875153
|View full text |Cite
|
Sign up to set email alerts
|

McCune-Albright Syndrome With Unremitting Hyperthyroidism at Early Age: Management Perspective for Early Thyroidectomy

Abstract: Background. McCune-Albright syndrome (MAS) is characterized by hyperpigmented macules, endocrinopathies, and fibrous dysplasia. Hyperthyroidism is the second most common endocrinopathy in MAS and its management is challenging, particularly among infants and toddlers. Traditionally, young infants have been treated with antithyroid medications, but remission is likely and these medications have severe side effects and affect the control of other endocrinopathies. Thus, it is reasonable to consider permanent trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…A literature review of eighteen articles dealing with thyroid surgery in paediatric population is shown in Table 3 [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Most studies (18) included in our literature review were retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A literature review of eighteen articles dealing with thyroid surgery in paediatric population is shown in Table 3 [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Most studies (18) included in our literature review were retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…Study period varied from 1 year [ 17 ] to 18 years [ 22 ]. Studies with the most patients were those in which partial or total thyroidectomy was usually performed [ 12 , 13 , 15 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], while fewer patients were included in studies that analysed robotic trans-axillary and retro-auricular approach [ 14 ] or transoral endoscopic thyroidectomy via vestibular approach [ 17 ]. The most common complication in all operations was hypocalcaemia due to incidental parathyroidectomy and recurrent laryngeal nerve injury.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As with all other manifestations of MAS, the activation of the stimulatory G protein is responsible for thyroid gland hyperplasia, thyroid hormone overproduction and increased conversion from T4 to triiodothyronine (T3). Clinically, this results in hyperthyroidism, goiter and/or thyroid nodules [178]. About 64% of MAS patients with thyroid alterations have nodular goiters, with nodules > 1 cm [176].…”
Section: Other Syndromesmentioning
confidence: 99%